Anatomy of the Cycladic Blueschist Unit on Sifnos Island (Cyclades, Greece). (July 2016) - Roche, Vincent; Laurent, Valentin; Cardello, Giovanni Luca; Jolivet, Laurent; Scaillet, Stéphane
Highlights: The CBU of Sifnos shows different degree of retrogression of HP-LT parageneses. Shearing was characterized by localization of strain toward the base of tectonic pile. Eocene shear zones were deformed and/or reactivated during post-orogenic exhumation with top-to-the-NE shearing. Late low-angle and steeper normal faults may be the brittle expression of the WCDS. The localization of strain occurred at the Eocene within the subduction channel. Abstract: Since 35 Ma, the kinematics of the Aegean domain has been mainly controlled by the southward retreat of the African slab, inducing back-arc extension. The main structures and associated kinematics are well constrained, but the kinematics of deformation before 35 Ma, coeval with the exhumation of blueschists and eclogites of the Cycladic Blueschist Unit, is still poorly understood. The earlier Eocene syn-orogenic evolution is strongly debated and very different geometrical interpretations and kinematic histories have been proposed in the literature. This study focuses on the high-pressure and low-temperature (HP-LT) parageneses spectacularly exposed and well preserved on Sifnos Island. The new field work provides new structural constraints on the tectonic history of HP-LT units generated in the subduction zone during the Eocene. It further shows how lithological heterogeneities localize strain within an accretionary wedge and how the localisation of strain evolves through time during exhumation. We show, through new geological and metamorphic maps, cross-sections and analyses of kinematic indicators, that Sifnos is characterized by shallow-dipping shear zones reactivating weak zones due to competence contrasts or earlier tectonic contacts. Structures and kinematics associated with these shear zones, show a top-to-the-N to −NE ductile deformation. The lower part of the tectonic pile shows a downward gradient of shearing deformation and is actually a thick top-to-the-NE shear zone, which we name the Apollonia Shear Zone. Through time shearing deformation tends to localize downward, leaving the upper part of the subduction complex preserved from late deformation. The present-day shape and topography of the island is largely controlled by late brittle faults reworking the earlier ductile shear zones. Comparing with the nearby island of Syros, we propose a new tectono-metamorphic evolution of the Cycladic Blueschist Unit, which partly explains the different degrees of retrogression observed on the Cycladic Islands.